Pandemic Factor in European Foreign Policy - Alexander Shumilin (Научно-аналитический вестник Института Европы РАН, 2020)
The article focuses on the problem of adapting the foreign policy of the European Union to the conditions of the world coronavirus pandemic. The author draws attention to the fact that the epidemic struck the EU countries at a time when the new leadership of the community had just begun to reform the main institutions in the spirit of the declared priorities, the main of which was to strengthen the role of the EU on the world stage. The strategic setting, however («build mus- cle») is faced with a new reality, dictated by the pandemic, which forced Brussels to return to its former «soft power» policy in international affairs. This policy is being implemented today in the form of «coronavirus diplomacy», but within the framework of the previously announced strategic points. Brussels is paying increased attention to its closest neighbors: member countries of the East- ern and Southern Partnerships and the Western Balkans. The bet on «soft power» in the form of humanitarian and financial assistance does not remove from the agenda the problem of EU rivalry, for example, with Russia and China with regard to some countries, in particular, Serbia. In this con- text, it seems unlikely that calls for solidarity in the fight against the pandemic will have an impact on the current state of relations between Russia and the European Union.